2017
DOI: 10.1186/s40479-017-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

Association among self-compassion, childhood invalidation, and borderline personality disorder symptomatology in a Singaporean sample

Abstract: BackgroundLinehan’s biosocial theory posits that parental invalidation during childhood plays a role in the development of borderline personality disorder symptoms later in life. However, little research has examined components of the biosocial model in an Asian context, and variables that may influence the relationship between childhood invalidation and borderline symptoms. Self-compassion is increasingly regarded as an adaptive way to regulate one’s emotions and to relate to oneself, and may serve to moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
1
12
0
1
Order By: Relevance
“…The model reached to explain only 26% of the variance in the BSL 23 scores. This amount of explained variance does not differ greatly from what was found by other studies using a similar approach (Keng & Wong, 2017;Robertson et al, 2013). In order to generate a better model, other important variables must be included.…”
Section: Discussionsupporting
confidence: 49%
“…The model reached to explain only 26% of the variance in the BSL 23 scores. This amount of explained variance does not differ greatly from what was found by other studies using a similar approach (Keng & Wong, 2017;Robertson et al, 2013). In order to generate a better model, other important variables must be included.…”
Section: Discussionsupporting
confidence: 49%
“…Linehan’s biosocial theory [ 49 ] suggests that what she calls "invalidating environments" during childhood may play an important role in the subsequent development of BPD in adolescence, by hindering the development of self-compassion and emotion-regulation. However, a study [ 50 ] found that even though childhood parental invalidation and lack of self-compassion are both strongly associated with BPD symptoms, their associations with BPD symptoms are independent of each other. In contrast, traumatic experiences may contribute to a self-invalidating and self-critical cognitive style [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abuses do harm to people's physical and mental health development, resulting in impaired mentalization and problematic behaviour. Also, the abuse that happened in childhood has long-term effects and leads to borderline personality disorder traits and co-occurring mental disorders [9] [10]. In Keng and Wong's study, child abuse has a great predictor and effect on the formation of borderline personality disorder [9].…”
Section: Abusesmentioning
confidence: 99%
“…It contributes to the childhood invalidation and formation of early borderline personality disorder. Also, borderline personality disorder patients frequently report that they have experienced child abuse [9]. For example, women who have suffered from child abuse or childhood trauma are two times more likely to have a cluster B personality disorder [11].…”
Section: Physical Abusesmentioning
confidence: 99%